2014
DOI: 10.1016/j.rbmo.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and prediction of IUI success in male subfertility: a systematic review

Abstract: Many variables may influence success rates after intrauterine insemination (IUI), including sperm quality in the native and washed semen sample. A literature search was performed to investigate the threshold levels of sperm parameters above which IUI pregnancy outcome is significantly improved and/or the cut-off values reaching substantial discriminative performance in an IUI programme. A search of MEDLINE, EMBASE and Cochrane Library revealed a total of 983 papers. Only 55 studies (5.6%) fulfilled the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 70 publications
10
123
1
3
Order By: Relevance
“…The studied correlation of sperm morphology with fertility links abnormal sperm shape to reduced oocyte fertilization for in vitro fertilization 42, 43. However, other correlations, such as the relationship between the shape of sperm and natural conception rates, have been much harder to demonstrate 44, 45. This microfluidic study offers new evidence that sperm morphology is indeed a significant factor in sperm transport in vitro.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The studied correlation of sperm morphology with fertility links abnormal sperm shape to reduced oocyte fertilization for in vitro fertilization 42, 43. However, other correlations, such as the relationship between the shape of sperm and natural conception rates, have been much harder to demonstrate 44, 45. This microfluidic study offers new evidence that sperm morphology is indeed a significant factor in sperm transport in vitro.…”
Section: Resultsmentioning
confidence: 84%
“…To understand sperm motility in such complex geometries, many hydrodynamic models have been developed at different scales;35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45 however, to the best of our knowledge, no models exist that can bridge the necessary time and length scales to allow the modeling of clinically relevant microfluidic ARTs and improve their design parameters. Here, we designed a filter‐like microfluidic path using multiscale computer simulations in conjunction with experiments and examined how this artificial path of pillars interact with known descriptive and functional characteristics of human sperm, including sperm motility, morphology, DNA integrity, and methylome status.…”
Section: Introductionmentioning
confidence: 99%
“…When it came to male factor consideration, attaining 5 million motile sperm threshold for IUI is recommended [21,28], while there is no consensus on a lower limit of semen quality at which one would advocate IUI [29];the systematic review confirms favourable correlation with IUI success in the range of 5-10 million [30].…”
Section: Discussionmentioning
confidence: 99%
“…It must be remembered that Total Motile Sperm Count [TMSC] inseminated has been cited as the most predictive index of conception after IUI cycles [9][10][11]. A minimalTMSC of 1 million for insemination was initially reported to be a requirement for pregnancy after insemination [12], but the systematic review of the literature by Ombelet et al in 2014 indeed confirms that the native sperm TMSC which shows the best correlation with IUI success is in the range of 5-10 million [6,[13][14][15][16]. According to a previous study, sperm concentration above 10 million is not related to further improvement in conception rates [12], while other investigators have reported the best pregnancy rates when more than 10 million motile spermatozoa are inseminated [9,17].…”
Section: Influence Of Semen Qualitymentioning
confidence: 99%
“…Intrauterine Insemination [IUI] is considered the simplest and least invasive procedure with reasonable live birth rates and not needing expensive infrastructure [1]. Inseminations have been done in domestic and farm animals since the 1900's while human artificial inseminations began in the 1940's [2].…”
Section: Introductionmentioning
confidence: 99%